Metamizole Utilization and Expenditure During 6-Year Period: Serbia vs. Croatia - Miljkovic, Milijana; Dragojevic-Simic, Viktorija; Rancic, Nemanja; Simic, Radoje; Pekez-Pavlisko, Tanja; Kovacevic, Aleksandra; Stamenkovic, Dusica (Frontiers in Public Health, 2018)
Background: Metamizole is a medication with analgesic, antipyretic, spasmolytic, and weak anti-inflammatory effects. The aim of our study was to evaluate a six-year trend in the utilization and expenditure of metamizole in comparison to other group of licensed non-opioid analgesics in Serbia and Croatia, in order to rationalize its use and prescribing in these countries. Methods: The data of metamizole versus all other non-opioid analgesics utilization and expenditure in Serbia and Croatia was analyzed according to the WHO methodology and expressed as defined daily doses per 1000 inhabitants per day (DDD/1000 inhabitants/per day) and total costs, respectively, during the six-year period from 2010-2015. Results: In the observed period, utilization of metamizole was 3.31 fold higher in Serbia than in Croatia (median in Serbia was 2.238 vs. 0.675 in Croatia DDD/1000 inhabitants/per day/per year). Expenditure of metamizole in the same period was 5.29 fold higher in Serbia than in Croatia (median in Serbia was 1,738,192.51 €/per year vs. 328,355.03€/per year in Croatia). Conclusion: Utilization and expenditure of non-opioid analgesics, including metamizole, in Serbia was significantly higher comparing with Croatia. Further research is needed to determine whether the current analgesic consumption in Serbia meets the needs of the patient. The benefits of metamizole should be weighed against the risk of metamizole-induced adverse effects. Until then, its prescribing should be based on indications and the appropriate duration of therapy.